Cover Image. (2nd August 2022) - Zhou, Qiming; Huang, Jing; Gu, Lei; Lyu, Kai; Huang, Yuan; Yang, Zhou
Abstract : The cover image is based on the Original Article Predator kairomone triggers sexual reproduction of Daphnia population via increasing population density, by Qiming Zhou et al. https://doi.org/10.1111/fwb.13969 .